Thermal analysis as a control tool for ductile iron production - Quilumba, Ronny; Proaño, Patricia; Sotomayor, Oscar (Frontiers in Metals and Alloys, 2025)
In the production of ductile iron, it is essential to control the chemical composition of melting, as this directly affects mechanical properties and final microstructure of the fabricated parts. However, this may not be sufficient. Physical phenomena such as nucleation potential, eutectic solidification, and recalescence provide useful information for production of ductile iron. Thermal analysis is a tool that has emerged to meet this need. In this study, thermal sensor equipment is employed to capture real-time samples of the molten metal to analyze its cooling curve. This information is used to determine physical state of the material during the various subprocesses required to produce ductile iron parts. Nucleation potential is the most influential thermal analysis property in ductile iron production. Controlling it helps assess the effects of nodularization and inoculation. Additionally, it plays a key role in optimizing costs and product quality. The high recalescence and solidification variability indicate a predominantly hyper-eutectic behavior, suggesting that reducing inoculant use could improve quality by preventing shrinkage defects, primary graphite formation, and carbides while lowering costs.